Normalization of Necessity Legal Maxims in DSN-MUI Fatwas: An Empirical Analysis of Indonesian Sharia Economic Fiqh Methodology - Ahmad Musadad; Shofiyun Nahidloh; Baihaqi Baihaqi; Misno Misno; A Mufti Khazin; Tri Pujiati (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2026)
The rapid development of the Islamic finance industry requires adaptive legal reasoning capable of responding to the increasing complexity of modern economic transactions. In Indonesia, fatwas issued by the National Sharia Council of the Indonesian Ulama Council (DSN-MUI) play a crucial role in establishing the normative framework of Islamic economic practices. This study aims to examine the use of necessity-based legal maxims (qawÄÊ¿id al-á¸arÅ«ra) in DSN-MUI fatwas and to analyze their methodological implications for the development of contemporary Islamic economic jurisprudence. Employing a qualitative approach with documentary analysis and content analysis methods, this research analyzes 165 DSN-MUI fatwas issued during the early phase of Islamic economic development in Indonesia. The findings reveal that 89 fatwas, representing approximately 53.9% of the total sample, explicitly employ legal maxims related to necessity, harm removal, or urgent need as the basis of legal reasoning. The most frequently applied maxims include al-á¸arar yuzÄl, al-á¸arar yudfaÊ¿ bi-qadr al-imkÄn, and al-á¸¥Äjah tanzil manzilat al-á¸arÅ«ra. These maxims are predominantly applied within sectors characterized by high transactional complexity, particularly Islamic banking, Islamic capital markets, and modern financial industries. The findings indicate that necessity-based maxims no longer function solely as exceptional mechanisms in classical Islamic jurisprudence but have evolved into methodological tools for adapting Islamic law to the dynamics of modern economic systems. This study contributes to the theoretical discourse on Islamic legal methodology by highlighting the strategic role of qawÄÊ¿id fiqhiyyah in the evolution of contemporary fiqh al-muÊ¿ÄmalÄt